Prophet Muhammad's Legal Politics: A Review of Islamic Legal on the Leadership of the Prophet - Umar Bensheikh; Wahyudi, Feri Eko; Yunus, Muh (Mazahibuna: Jurnal Perbandingan Mazhab, 2022)
In the review of Islamic legal, Prophet Muhammad’s politics is an exciting theme to be studied more deeply. The Prophet Muhammad SAW was referred to as Ummī (illiterate), reinforcing the notion that the Prophet was not intelligent and capable. A qualitative method was conducted to prove how the Ummī Prophet was smart, trustworthy, full of wisdom, respected, and legally competent. In some of the legal provisions, Prophet PBUH presented a solution to the ilā ākhīr al-zamān, where the concept of social justice in upholding human rights was aggressively debated. Several requirements of the Prophet Muhammad’s sunnah, which obliged males to defend women and their rights, was established fourteen centuries ago. Likewise, the concept of tolerance and interfaith relations have been initiated. In addition to being a historical leader, the Prophet was once a judge in an infidel dispute and was regarded as a knowledgeable communal figure. Prophet SAW was given the authority to establish new laws for specific issues through sunnah on matters not determined by their legal provisions in the Qur’an.